2018
DOI: 10.1186/s12916-018-1017-7
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive designs in clinical trials: why use them, and how to run and report them

Abstract: Adaptive designs can make clinical trials more flexible by utilising results accumulating in the trial to modify the trial’s course in accordance with pre-specified rules. Trials with an adaptive design are often more efficient, informative and ethical than trials with a traditional fixed design since they often make better use of resources such as time and money, and might require fewer participants. Adaptive designs can be applied across all phases of clinical research, from early-phase dose escalation to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
481
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 523 publications
(490 citation statements)
references
References 141 publications
4
481
0
5
Order By: Relevance
“…In these situations, one could implement stratified randomization to separate them by allocating them to groups. Moreover, the investigator could use weighted/unequal randomization which is still randomized but results in fewer participants allocated to the experimental group (or nonexperimental group whichever is deemed to have adverse consequences) (adaptive design) 11,12 . There are alternative methods for designing the clinical trial which can be used, such as patient‐preferred clinical trials, or different approaches to randomizing people to the groups, such as adaptive design clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…In these situations, one could implement stratified randomization to separate them by allocating them to groups. Moreover, the investigator could use weighted/unequal randomization which is still randomized but results in fewer participants allocated to the experimental group (or nonexperimental group whichever is deemed to have adverse consequences) (adaptive design) 11,12 . There are alternative methods for designing the clinical trial which can be used, such as patient‐preferred clinical trials, or different approaches to randomizing people to the groups, such as adaptive design clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with best practice guidance on adaptive trial design, we had conducted extensive simulations and agreed a clear interim analysis plan approved by the DMEC. 162, 163 The interim analysis was based on a comparison of the change in QUALEFFO-41 score at 4 months and indicated that the mean 4-month improvement in QUALEFFO-41 score was greater for both exercise therapy and manual therapy than SSPT (mean differences of -2.20 and -0.74 points for exercise therapy and manual therapy, respectively), although the differences were not statistically significant. On the basis of these mean values, it was decided to continue with both intervention arms and the SSPT arm, following the planned decision rule.…”
Section: Internal Validity and Methodological Limitationsmentioning
confidence: 99%
“…The fact that engagement dropped substantially early within the constraint of a randomized controlled trial suggests that a more effective intervention, that automatically adapts to behavior and self-measured engagement such as using just in time adaptive design, may be needed. [34,35] …”
Section: Discussionmentioning
confidence: 99%